Deep oxidative–extractive desulfurization of fuels using benzyl‐based ionic liquid. Issue 11 (3rd June 2016) - Li, Mingxia; Zhou, Zhiyong; Zhang, Fan; Chai, Wenshuai; Zhang, Lele; Ren, Zhongqi
Abstract : Four benzyl‐based ionic liquids (ILs) were synthetized and used for deep desulfurization of model oil and real diesel fuel. The removal efficiencies of benzothiophene (BT) and dibenzothiophene (DBT) with [Bzmim][NTf2 ] and [Bzmim][SCN] as extractants are higher than that with [Bzmp][NTf2 ] and [Bzmp][SCN] as extractants. The desulfurization capability follows the Nernst's Law. A reactive extraction mathematical model for desulfurization was established. An oxidative‐extractive two‐step deep desulfurization method was developed. DBT was first oxidized by H2 O2 with CH3 COOH as catalyst and then the unoxidized DBT and uncrystallized dibenzothiophene sulfoxide (DBTO2 ) in model oil were extracted by [Bzmim][NTf2 ], and finally the removal efficiency was 98.4% after one‐stage extraction. Besides, the removal efficiency of 4, 6‐DMDBT was 96.4% after oxidation and one‐stage extraction processes. Moreover, the oxidative‐extractive two‐step deep desulfurization method was also effective for desulfurization of diesel fuel. The removal efficiency of sulfur reached up to 96% after oxidation and three‐stage cross‐current extraction processes. © 2016 American Institute of Chemical Engineers AIChE J, 62: 4023–4034, 2016